Średniowieczne rezydencje obronne Półkoziców w zachodniej Małopolsce. Wstęp do problematyki badań - Kołodziejski, Stanisław (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
Amont medieval feudal elite living in Little Poland the family of Półkozice held an important position in political and economic sphere. Unfortunately, historians have rather underrated their role and not worked up comprehensive historical records. The present article contributes slightly to the illustration of the effects of the Półkozice economic activities, which are evident in defensive foundations raised in the centres of estates. As historical researches proved, the earliest complex of properties were gathered by the family on the Raba near Niegowicia. Relics of the first fortified endowement were found in Chrostowa at the estuary of the Stradomka river to the Raba. Archaeological findings and analysis of written records enable us to assume that it was most probably founded in the end of the 13th century and fell into decline in the beginning of the 16th century. When the castle in Chrostowa diminished the Półkozice presumably erected a new defensive fortification in nearby Niewiarów. Yet, archaeologists have been unable to locate its remnants. The document from 1552 is the only source of information about this residential-economic complex. Another castle of the Półkozice family in Bobrek was not archaeologically examined either. The first record of a defensive site functioning there comes from the document from 1395, which mentions castrum in Bobrek. For over a few centures the residence was a possession of the Ligenza family bearing the Półkozic sign. The relics of another castle erected by the Półkozice lie in Wrocimowice. Either in here archaeological excavations have not been carried out. The results of reconnaissances and studying medieval documents make us possible assume that the fortification was built in the 14th century and decreased most likely in the 16th century. Archaeological researches embraced two other settlements of the Półkozice. The first was raised in the 14th century on the hill in Wielka Wieś, on the left bank of the Dunajec. The other defensive residence is assumed о have been founded in the 14th century as well in Brzezówka at the mouth of the Jasiołka to the Wisłoka river. At around that time, i.e. about half of the 14th century, the family constructed the castle in Będziemyśl near Rzeszów. Its relics have been recently assessed by excavatory methods. The foundation in Czyżów Szlachecki on the left bank of the Vistula is the foremost northern castle. Written records date back its raising to the beginning of the 15th century. The characterized foundations of the most eminent members of the Półkozice mentioned in this article need further archaeological researches. Historians-medievalists should thoroughly elaborate on their history as well.